2020
DOI: 10.1371/journal.pone.0238588
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal communication in selfies posted on Instagram: Another look at the effect of gender on vertical camera angle

Abstract: Background Selfies are a novel social phenomenon that is gradually beginning to receive attention within the cognitive sciences. Several studies have documented biases that may be related to nonverbal communicative intentions. For instance, in selfies posted on the dating platform Tinder males but not females prefer camera views from below (Sedgewick, Flath & Elias, 2017). We reexamined this study to assess whether this bias is confined to dating selection contexts and to compare variability between individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have reported that choices of camera angle are related to the sex of the taker, with males preferring angles from below and female preferring angles from above or at eye-level (Sedgewick, Flath & Elias, 2017, Bruno, Uccelli, Pisu et al, 2020. In addition, a related study provided some evidence that camera angle is modulated by communicative intention, such that angles from above become less frequent in female sel es posted on Tinder in comparison to Instagram (Soranzo & Bruno, 2020). These effects have been interpreted in relation to the expressiveness of views from below, which may be associated with dominance, in contrast to views from above that may be associated to submission.…”
Section: Discussion Conclusionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies have reported that choices of camera angle are related to the sex of the taker, with males preferring angles from below and female preferring angles from above or at eye-level (Sedgewick, Flath & Elias, 2017, Bruno, Uccelli, Pisu et al, 2020. In addition, a related study provided some evidence that camera angle is modulated by communicative intention, such that angles from above become less frequent in female sel es posted on Tinder in comparison to Instagram (Soranzo & Bruno, 2020). These effects have been interpreted in relation to the expressiveness of views from below, which may be associated with dominance, in contrast to views from above that may be associated to submission.…”
Section: Discussion Conclusionmentioning
confidence: 93%
“…Despite the popularity of the face mask sel e subgenre, however, there has been essentially no research on the impact of masks on sel e taking behaviors. Evidence bearing on this issue is interesting not only on a general level, as an extension of existing data on masks and interpersonal communication in presence, but also as a test of models that seek to understand how non-verbal communication in sel es may be modulated by different communicative intentions and other contextual factors (Bruno, Pisanski, Sorokowska & Sorokowski, 2018;Bruno, Uccelli, Pisu et al, 2020;Soranzo & Bruno, 2020). Speci cally, in the current study we purported to do four things.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Further, Yau and Reich (32) argued that social media provides individuals more time to edit and craft their posts to allow for purposeful and even strategic self-presentation and impression management. In images, meaningful self-expression not just arises from the content, but also composition or camera manipulation, including camera tilt and distance to the object (33,34). Images can offer particularly interesting insights in psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction Social media's rapid proliferation has fashioned the taking and sharing of selfies as ubiquitous (Grindstaff and Torres Valencia, 2021;McLean et al, 2019), where the word "selfie" has become renowned in the digital world (Faimau, 2020) as a novel social phenomenon (Soranzo and Bruno, 2020). Selfies are defined as self-portraits that visually communicate (Hess, 2015) and represent an individual's (Jackson, 2019;Qiu et al, 2015) thoughts, beliefs, and creativity (Karwowski and Brzeski, 2017), and it has arisen as a culture fixated with itself (Hess, 2015).…”
mentioning
confidence: 99%